2015
DOI: 10.1055/s-0035-1563385
|View full text |Cite
|
Sign up to set email alerts
|

Chest Physiotherapy in the Pediatric Intensive Care Unit

Abstract: Despite widespread practice, there is very little, high-level evidence supporting the indications for and effectiveness of cardiopulmonary/chest physiotherapy (CPT) in critically ill infants and children. Conversely, most studies highlight the detrimental effects or lack of effect of different manual modalities. Conventional CPT should not be a routine intervention in the pediatric intensive care unit, but can be considered when obstructive secretions are present which impact on lung mechanics and/or gaseous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 120 publications
0
14
0
1
Order By: Relevance
“…Current evidence is insufficient to provide strong recommendations for chest physiotherapy in the PICU. [156,157] Summary: High care and intensive care of children with pneumonia…”
Section: Physiotherapymentioning
confidence: 99%
“…Current evidence is insufficient to provide strong recommendations for chest physiotherapy in the PICU. [156,157] Summary: High care and intensive care of children with pneumonia…”
Section: Physiotherapymentioning
confidence: 99%
“…Current evidence is insufficient to provide strong recommendations for chest physiotherapy in the PICU. [66,67] Summary: High care and intensive care of children with pneumonia…”
Section: Physiotherapymentioning
confidence: 99%
“…In addition to facilitating secretion clearance, mobilisation and active exercise aim to improve thoracic mobility; increase lung volume; improve or maintain cardiovascular fitness, exercise tolerance and muscle strength; prevent postural deformities; improve bone ossification, bladder and bowel function; maintain skin integrity and confer psychological benefits (Button & Button 2013; Morrow 2015:174–181). Mobilisation techniques and exercise prescription should be selected according to the individual patients’ general condition, chronological (or corrected) age and developmental level (Morrow 2015:174–181). The term ‘mobilisation’ includes a range of active, passive or assisted techniques, including limb exercises, bed mobility, sitting out of bed, standing, crawling and walking.…”
Section: Airway Clearance Techniquesmentioning
confidence: 99%
“…In critically ill adults, percussion has been associated with cardiac arrhythmia and a decrease in pulmonary compliance (Stiller 2000:1801–1813), and it has been suggested that both percussion and vibrations may cause or exacerbate bronchospasm (Kirilloff et al 1985:436–444). In acutely ill children, any potential benefits of intervention must be carefully balanced against risk of harm before they are implemented (Morrow 2015:174–181). From personal experience, some children enjoy percussion and tolerate it well, while in others there may be a perception of the perpetuation of physical abuse (hitting), a problem that is rife in our community.…”
Section: Airway Clearance Techniquesmentioning
confidence: 99%